2012
DOI: 10.1134/s0021894412030200
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory observation of slow movements in rocks

Abstract: Results of uniaxial compression tests of rock samples in electromagnetic fields are presented. The experiments were performed in the Laboratory of Basic Physics of Strength, Institute of Continuous Media Mechanics, Ural Branch of RAS (ICMM). Deformation of samples was studied, and acoustic emission (AE) signals were recorded. During the tests, loads varied by stages. Specimens of granite from the Kainda deposit in Kyrgyzstan (similar to samples tested at the Research Station of RAS, hereafter RS RAS) were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
2
4
0
3
Order By: Relevance
“…Realization of one of the shapes of localized strain fields in the sylvinite specimen under tension depends on the level of the applied stress, which correlates with the previous results obtained for a number of rocks, metals and alloys [2,14].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Realization of one of the shapes of localized strain fields in the sylvinite specimen under tension depends on the level of the applied stress, which correlates with the previous results obtained for a number of rocks, metals and alloys [2,14].…”
Section: Resultssupporting
confidence: 65%
“…Earlier, in [2], it has been shown that the plastic flow in some rocks under quasistatic compression remains localized over the whole period of the deformation process up to the sample fracture. The forms of macrolocalization are governed by the strain hardening laws operating at the corresponding stages of the process.…”
Section: Introductionmentioning
confidence: 98%
“…9). В течение эксперимента процесс деформирования образца носит неоднородный характер и происходит в виде последовательно распространяющихся по поверхности образца медленных волн локализованной деформации [Zuev, 2011;Zuev et al, 2012]. При этом наблюдаются волны локализованной поперечной деформации (волны, в которых частицы материала перемещаются в направлении, перпендикулярном направлению сжатия) и волны локализованной продольной (осевой) деформации (рис.…”
Section: результаты исследованияunclassified
“…При этом наблюдаются волны локализованной поперечной деформации (волны, в которых частицы материала перемещаются в направлении, перпендикулярном направлению сжатия), и волны локализованной продольной (осевой) деформации. Наблюдаемые волны локализованной деформации являются «медленными», скорость их распространения на шесть-семь порядков меньше характерной скорости звука в материале, что соответствует ранее полученным результатам исследования форм локализации деформации при нарушении горных пород [Zuev, 2011;Zuev et al, 2012].…”
unclassified
“…Concurrently with the deformation plotting, using the speckle photography technique and ALMECtv software system [1], we recorded localization of deformation at a face of the specimens in a similar manner as in [15,16]. This method allows calculation of all components of the plastic distortion tensor r ∇ (r-displacement vector assessed by the speckle images), but we limit ourselves to the axial strain The main behavioral feature of the localized strain zones was their displacement along the specimen in the linear section of σ -ε curve as the total strain grows.…”
mentioning
confidence: 99%